»Kaj si pa ti kot politik naredil za ta uspeh?!«: Raba strokovnega jezika diplomacije med poslankami in poslanci državnega zbora v letih od 1990 do 2018 - Udovič, Boštjan (Slavia Centralis, 2025)
“How did you as a Politician Contribute to this Success?”: The Use of the Language of Diplomacy among Members of the National Assembly between 1990 and 2018. The aim of this article is to establish how the members of the National Assembly use specialised terminology in the field of diplomacy. Results of quantitative and qualitative analyses show that in their speeches MPs (1) often use technical terms from the field of diplomacy incorrectly or semi-colloquially; (2) when talking about the field of diplomacy, they often resort to journalistic language rather than the language of the profession; and (3) they use political language based on colloquialisms.